Rubber Dam and Application Methods in Dental Practice - Eskibağlar, Mehmet; Karaağaç Eskibağlar, Büşra; Gündoğar, Mustafa; Özyürek, Taha (Selcuk University, 2021)
Isolation is necessary in most dental practices. Rubber dam method is often preferred for this process. Rubber dam improves the success of the process by providing proper isolation of the study area. In addition, it reduces aerosol formation. Today, it protects of the operator and the dental staff and the patients from infectious diseases such as coronavirus transmitted by droplets. By optimizing the way it works, it prevents possible soft mouth tissue injuries that you choose from the operator’s view. In this review article, rubber dam isolation method which is used frequently in dentistry is explained. © 2021, Selcuk University. All rights reserved.
Diş Hekimliği Pratiğinde Rubber Dam ve Uygulama Yöntemleri
Keywords: Dentistry; Rubber dam; İsolation